Entrepreneurial strategic processes - Lumpkin, G. T.; Katz, Jerome A. (Advances in entrepreneurship, firm emergence and growth ;, 2007)
Entrepreneurial value creation requires that organizations understand both the actions they need to take and how to effectively take them. The dynamic nature of entrepreneurial behavior involves not only the strength or uniqueness of a firm's resources and competencies but also the capabilities and processes needed to create value and appropriate wealth. This distinction has served the fields of strategy and entrepreneurship well because it provides scholars with a framework for investigating the relationship between the elements of competitive superiority (content) and the decision making styles and practices (processes) involved in taking action and implementing change. On the path from opportunity recognition to new value creation to wealth appropriation, entrepreneurial strategic processes are among the most important steps. The purpose of this volume is to focus on the entrepreneurial processes that have the greatest impact on strategic outcomes such as organizing, learning, and contributing to outstanding financial performance. The chapters draw on both scholars new to the field as well as some of those who have previously made significant contributions to entrepreneurial process research. Several chapters address entrepreneurial processes in a corporate setting including both large and medium-sized corporations. Other chapters explore the issues faced by entrepreneurial owners and managers in directing both themselves and their organizations. Another topic of this volume is the distinctive entrepreneurial process challenges of young and small firms.